(untitled) (ex æquo, 2023)
For, against, or somewhere in the middle? Positions and discourses of board members about legally binding thresholds of representation, merit and equality This paper seeks to analyse the positions and discourses of board members serving in companies that are legally bound by a minimum balanced threshold of representation between men and women. The results show that, despite the lack of a marked opposition to legally binding affirmative action measures, the current Law is far from consensual. The greater opposition and resistance is voiced by male board members, while female board members make up the majority of those who contradict the narrative that binding measures may compromise meritocracy. Women tend to deny any experience of discrimination throughout their professional careers, but, contradictorily, they also admit having to provide more proof of competence than their male colleagues. Such a narrative suggests that the conditions in which they serve on boards is still pervaded by inequality in relation to their male peers.